Implications of age in mammographic density interpretation - Ben Geweref, Nadya; Kutrani, Faiza; Elbagermi, Nadeia; Eljabali, Ebtisam; Buzgheia, Mohamed; Beheh, Ali; Latawash, Ali (Libyan Journal of Science &Technology, 2022)
Abstract Objective. The importance of breast density correlated with its significant impaction in Mammogram’s interpretation and to the increased risk of development of breast cancer, we examined the breast density of 1051 of screening and diagnostic Mammography in Mammography unit in Benghazi medical center, our study aimed to find the relationship between the age and mammographic breast density. Materials and Methods. This is a retrospective review of the diagnostic and screening Mammography underwent in Benghazi Medical Center’s in Mammography unit during 2016-2917. Analysis of variance and descriptive analyses were used to evaluate the relationship between patient age and breast density. Results. A total of 1051 women were examined by digital mammography at Department of Radiology in Benghazi Medical Center during the period from 2016-2017, the women age was ranged from 22 to 88 years with a median age of 48 years, the subgroups are Classified by the age decade, and we find that the relationship between the age and the breast density is significant inverse relation (p=0.000) 60.9% of patients between40 and 49 years old had dense breasts. and it reduced to 36.6% of women in their 50s. However, 28.7% of females in their 60s and 5.3% of patients in their 70s had dense breasts as interpreted on their screening and diagnostic mammograms. Conclusion. We found that the age of the patient and the breast density are related inversely, but the interest is that we also found extreme value at the extremes of age where a considerable percentage of young women had mostly fatty tissue rather than glandular tissue and at the same time there's also a meaningful group of old women has dense breast tissue instead of fatty tissue.